Rehabilitation Exercise in Persons with Stable Heart Failure - Boonyarat, Ammarawadee (Nursing Research and Innovation Journal, 2018)
Abstract: The purpose of this article was to review, analyze, and summarize research studies and articles related to the benefits, guidelines, and methods of rehabilitation exercise in patients with stable heart failure. The literature used for this article was reviewed and selected from reliable evidence studies aiming to recommend practice guidelines for rehabilitating stable heart failure patients. The review revealed that rehabilitative exercise is reasonable and beneficial for persons with stable heart failure. An appropriate and safe exercise includes three phases: 1) the warm-up phase, 2) the conditioning phase, and 3) the cool-down phase. The criteria to recruit heart failure patients eligible to follow this protocol were those who can perform functional ability at the New York Heart Association (NYHA) class II-III, and 2) those who do not have any apnea during resting or exercising period for at least 3-5 days prior to rehabilitation. The type of exercise includes: 1) aerobic exercise, 2) resistance training, and 3) a combination of aerobic exercise and resistance training. The goal of intensity is at the low to moderate levels, 40% to 85% of maximum heart rate at exercise or 50% to 85% of maximal oxygen consumption or the Borg Scale of Perceived Exertion as the score of 12-16. The exercise duration should be 20 to 40 minutes. At first, the exercise should take a shorter period of time. In another word, the exercise should last at least 10 minutes at the beginning and the duration and intensity of the exercise should gradually increase until the target goal is reached. The frequency of exercise should be 3 to 7 days per week and continuously done for at least 4 weeks. To be productive, in terms of reducing the hospital readmission and mortality rates, persons with stable heart failure should exercise for a continuous period of at least 6 months to 1 year and should be under the supervision of healthcare providers who have knowledge in this area. This literature review is expected to be useful to clinical application in educating, promoting, supporting and caring for persons with heart failure to achieve better health status and quality of life. Keywords: Congestive Heart Failure, Type of exercise, Intensity of exercise, Frequency of exercise, Duration of exercise